Solar cooking in Kenya - Abdul Sater, Alaa; Tolly, Johanna (My University, 2021)
This is a master thesis in Industrial Design Engineering written at the Department of Industrial and Materials Science, in the end of 2020 and beginning of 2021. Almost three billion people use some kind of fuel to cook over open fires and as a result breathe in harmful smoke, which causes millions of deaths each year. Engineers Without Borders have initiated a project concerning solar cooking, since making use of free and available solar energy as a source when cooking has proved to both help fight poverty and decrease the risk of exposing the users to danger. Kenya has been the centre of operating solar cookers in East Africa and it is decades old in the country. Despite this much less than 1% of the population uses it. In this project an extensive take on the situation of today in Kenya has been made in order to identify obstacles to solar cooker diffusion. The aim of the project was to increase the understanding of today’s user situation and develop a concept that intends to contribute to an increased solar cooking diffusion in Kenya. Overall, the project followed a workflow of design thinking with iterations of the various phases. Through the theories of diffusion of innovations and domestication, user issues connected to the usage of solar cookers were investigated. Some of the methods used for conducting the research was analysing previous solar cooker project evaluations, collaborating with representatives from organisations engaged in solar cooking and interviewing the targeted user. This resulted in different identified problem areas, such as the material and the construction of the solar cooker being too vulnerable in order to withstand the user environment. The intention of the presented user journey was to give a vivid description of the situation of today with the solar cooker and target group put in a realistic context. Three design concepts were created in an attempt to solve the most prominent product issues. One final concept was chosen, mainly because of its durability properties. The concept was named JiKoni (jiko=stove and koni=cone) and it is a type of panel solar cooker called conical cooker. The conical cooker was chosen since that type of cooker suits the geographical placement of Kenya in relation to the sun. The conical cooker was also considered to have great development potential, seeing that there are few but appreciated versions available today. JiKoni was created to withstand the user environment and to make the user feel safe to leave it during its time-consuming cooking. The concept is estimated to be more expensive compared to solar cookers that are usually used today but the benefits of a more durable cooker, in terms of e.g., being able to keep it for a longer period of time without frequent need of repairs, are meant to outweigh the price. This is meant to decrease the diffusion of solar cooking in Kenya since a product that could be used more also will be more exposed to others. The more the product is visible and appreciated, the more likely it is that other people will be willing to adopt it.